Rapid Identification of Chemical Constituents in Hericium erinaceus Based on LC-MS/MS Metabolomics - Fei Yang; Honglin Wang; Guoquan Feng; Sulan Zhang; Jinmei Wang; Lili Cui (Journal of Food Quality)
Hericium erinaceus is a precious edible and medicinal fungus with high nutritional value. It has many functions, such as enhancing immunity, antitumor antioxidation, antihyperglycemic, antihyperlipidemic, and protecting gastric mucosa. However, there are few researches about the H. erinaceus compounds. In this paper, ultraperformance liquid chromatography tandem high-resolution mass spectrometry (UPLC-Q-exactive-MS/MS) was used to isolate and identify the compounds in H. erinaceus. 102 compounds were identified in H. erinaceus by comparing with standard databases such as MZVault, MZCloud, and BGI Library (self-built standard Library by BGI Co., Ltd), including flavonoids, terpenoids, phenolic acids, phenylpropanoids, steroids, organic acids, and amino acids.